Clinical Practice Guidelines for Acute Myocardial Infarction. - Francisco De Jesús Valladares Carvajal; Arelys Falcón Hernández; Félix Rolando Jorrín Román; Juan Emilio García Rivas (Medisur)
Clinical Practice Guidelines for Acute Myocardial Infarction. It has been defined as the clinical condition caused by the ischemic myocardial necrosis, usually caused by abrupt reduction of coronary blood irrigation affecting one or more myocardial areas. The document includes a review and update of the concept, classification, diagnosis and therapy. Risk stratification and main aspects of rehabilitation are also stressed. It includes assessment guidelines focused on the most important aspects to be accomplished.